Chemical kinetic modelling of ammonia/hydrogen/air ignition, premixed flame propagation and NO emission. (15th June 2019) - da Rocha, Rodolfo Cavaliere; Costa, Mário; Bai, Xue-Song
Highlights: Chemical kinetic modelling of combustion of ammonia/hydrogen/air mixtures. Addition of H2 to NH3 flames increases exponentially flame speed and NOx emissions. Existing mechanisms predict scattered ignition delay times, flame speeds, and NOx . NO formation is mainly produced through the NH3 /O2 chemical process. Mechanisms' differences due to relative importance of NNH and HNO sub-mechanisms. Abstract: This work reports on a study of chemical kinetic modelling of ammonia/hydrogen/air ignition, premixed flame propagation and NO emission. A survey of chemical mechanisms available in the literature was first conducted, and the performance of 10 mechanisms was analysed in terms of the prediction of shock tube ignition delay times, laminar flame speeds and NOx concentrations for NH3 /air and NH3 /H2 /air flames for a wide range of operating conditions. Then, three of these mechanisms were reduced and their performance compared against the behaviour of the original mechanisms. The results confirm that pure NH3 flames have high ignition delay times and rather low flame speeds, and that the addition of H2 to NH3 flames increases exponentially the flame speed, and significantly the NOx emission. The currently available chemical kinetic mechanisms predict rather scattered ignition delay times, laminar flame speeds, and NOx concentrations in NH3 flames, indicating that improvements in the sub-mechanisms of NH3 and NH3 /H2 oxidation are still needed. Sensitivity analysis for NO formation indicates that NO formation in NH3 flames is mainly produced through the NH3 /O2 chemical process, and sensitivity analysis for flame speed reveals that the differences among mechanisms are due to the relative importance of the reactions of the NNH and HNO sub-mechanisms. The reduced mechanisms show high fidelity when compared with the original ones, despite some discrepancies at high pressures.